2022
DOI: 10.17235/reed.2022.8795/2022
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive protein postoperative values to predict clinically relevant postoperative pancreatic fistula after distal pancreatectomy

Abstract: IntroductionDespite significant medical and technological advances, the incidence of Postoperative pancreatic fistula (POPF) after distal pancreatectomy (DP) is reported to be between 3-45%. The main objective of our study was to analyse the early post-surgical risk factors for developing POPF after DP. Material and methodsA retrospective observational study was conducted on a prospective basis of patients undergoing PD in a tertiary hospital from January 2011 to December 2021. Sociodemographic, preoperative a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…In our results, we found a significantly increased CRP in patients with anaemia. However, some authors found this condition to be often associated with postoperative inflammatory complications; the relation to anaemia is currently not clear enough [ 39 , 40 ]. Preoperative anaemia workup must be standard before distal pancreatectomy.…”
Section: Discussionmentioning
confidence: 99%
“…In our results, we found a significantly increased CRP in patients with anaemia. However, some authors found this condition to be often associated with postoperative inflammatory complications; the relation to anaemia is currently not clear enough [ 39 , 40 ]. Preoperative anaemia workup must be standard before distal pancreatectomy.…”
Section: Discussionmentioning
confidence: 99%